Optimizing the solvent extraction process for high-value compounds from sweet cherry press cake treated with pulsed electric fields using response surface methodology - Rrucaj, Ervehe; Carpentieri, Serena; Siano, Francesco; Ferrari, Giovanna; Pataro, Gianpiero (Frontiers in Food Science and Technology, 2023)
Cherry juice production generates substantial cherry processing by-products, presenting a significant environmental challenge. The valorization of these by-products can not only reduce management costs but also enhance profitability by recovering valuable intracellular compounds. This study aimed at the extraction of bioactive compounds with potent antioxidant activity from sweet cherry press cake using Pulsed Electric Fields (PEF)-assisted extraction. PEF pre-treatment, carried out using a predetermined field strength (E = 3 kV/cm) and total specific energy input (WT = 10 kJ/kg), was applied to the cherry press cake prior to the subsequent solid-liquid extraction (SLE) stage. To optimize the SLE process for both untreated and PEF-treated samples, Response Surface Methodology (RSM) was employed to determine the most effective extraction parameters, including extraction temperature (20-50 °C), solvent concentration (0-50% ethanol in water), solid-liquid ratio (0.05-0.2 g/mL), and diffusion time (30-360 min). The objective was to maximize key response variables: total phenolic content (TPC), flavonoid content (FC), total anthocyanin content (TAC), and antioxidant activity (FRAP). The extracts obtained from both untreated and PEF-treated samples under optimal conditions underwent HPLC-DAD analysis. The results revealed that, under optimized SLE conditions (50 °C, 50% ethanol-water mixture, 0.2 g/mL solid-liquid ratio, and 360 min extraction time), PEF pre-treatment significantly enhanced the extractability of high-value compounds. This resulted in notable increases in TPC (+26%), FC (+27%), TAC (+42%), and antioxidant activity (+44%) compared to conventional SLE. Additionally, the application of PEF reduced extraction time (by 5-18 min) and solvent usage (by 2%). HPLC analysis This is a provisional file, not the final typeset article identified cyanidin-3-O-rutinoside as the predominant phenolic compound in both untreated and PEFtreated extracts, with a remarkable increase (+2.3-fold) after PEF application. These findings underscore the potential of PEF-assisted extraction as a promising approach to maximize the recovery of valuable compounds from sweet cherry press cake, contributing to food waste reduction and enhanced value generation from by-products.